Професор Б.Мартос: організаторська та науково-педагогічна діяльність - Уткін, О. (Український історичний журнал, 2021)
Мета статті полягає в аналізі організаторської та науково-педагогічної діяльності
Б.Мартоса, спрямованої на становлення й розвиток незалежної України, формування
національного консенсусу в період Української революції 1917–1921 рр. В еміґрації він
став одним із засновників і керівників Української господарської академії, Українського
технічно-господарського інституту. Займався підготовкою економістів, науково-дослідною
роботою в галузі економіки, теорії та практики кооперації, а також громадською діяльністю.
Методологічну
основу становлять принципи історизму, об’єктивності, науковості. Використовувалися
загальнонаукові
(аналіз, синтез, узагальнення), а також методи періодизації
і класифікації. Їх застосування дозволило об’єктивно відобразити діяльність урядових
структур УНР 1917–1920 рр., українських вишів в еміґрації, де працював Б.Мартос. Спеціальні
історичні методи (архівознавчого та джерелознавчого аналізу, персоналізації,
історико-логічний, біографічний) сприяли здобуттю нових знань з історіографічних, архівних,
біографічних матеріалів, визначенню
їх цінності. Висновки. Доведено, що активна
державницька, політична і громадська діяльність Б.Мартоса під час перебування на посадах
міністра продовольчих справ, фінансів, голови Ради Народних Міністрів часів УЦР та
Директорії зосереджувалася на відновленні й розбудові національної державності у формі
демократичної республіки, захисті національних інтересів України, вирішенні найважливіших
політичних і правових проблем. Цій меті служила його організаторська, педагогічна, науково-
дослідницька діяльність у галузі економіки, теорії формування та функціонування кооперації,
організації і проведення навчально-виховної роботи. The aim of the article is to analyze B.Martos’ organizational and scientificpedagogical
activities, focused on the formation and development of a democratic independent
Ukraine, the formation of national consensus during the Ukrainian Revolution. He often acted
as a confrontational factor, especially with regard to the Western Ukrainian People’s Republic,
conducting scientific research. After the defeat of the revolution, he found himself in exile, where
he became one of the organizers and leaders of the Ukrainian Academy of Economics and the
Ukrainian Technical and Economic Institute. He was engaged in the training of highly qualified
economic personnel, research work in the field of economics, theory and practice of cooperation,
as well as public activities. The methodological basis is the principles of historicism, objectivity,
science. The general scientific methods (analysis, synthesis, generalization), periodization and
classification were used. The application of these methods contributed to the objective, scientific
reflection of the activities of a number of governmental structures of the Ukrainian People’s
Republic 1917–1920, Ukrainian universities in exile, where B.Martos worked, the results of his
work in different periods. Special historical methods (archival and source analysis, personalization,
historical-logical, biographical) served as a way to obtain new knowledge from historiographical,
archival, biographical materials, determine their value, place in the intellectual achievements
of scientists of the Ukrainian diaspora and the world scientific community. Conclusions. It is
proved that the active state, political and public activity of B.Martos as Minister of Food, Minister
of Finance, Chairman of the Council of People’s Ministers in governmental structures of the
Ukrainian Central Council and the Directory focused on restoring and building national statehood
in the form of a democratic republic, protection of Ukraine’s interests, the solution of political and
legal problems, lawmaking. B.Martos’ organizational, pedagogical and research activities in the field
of economics, the theory of formation and functioning of cooperation, organization and conduct
of educational work was aimed at achieving this goal.